MAX phases : properties of machinable ternary carbides and nitrides - Barsoum, Michel W. (Wiley-VCH, 2013)
In this comprehensive yet compact monograph, Michel W. Barsoum, one of the pioneers in the field and the leading figure in MAX phase research, summarizes and explains, from both an experimental and a theoretical viewpoint, all the features that are necessary to understand and apply these new materials. The book covers elastic, electrical, thermal, chemical and mechanical properties in different temperature regimes. By bringing together, in a unifi ed, self-contained manner, all the information on MAX phases hitherto only found scattered in the journal literature, this one-stop resource offers researchers and developers alike an insight into these fascinating materials.